Sultan Ageng Tirtayasa University and Its Impact on Social Economy - Sugeng Setyadi; Deris Desmawan; Rizal Syaifudin; Anita Widiastuti (Economics Development Analysis Journal, 2021)
The purpose of this research is to analize the impact of Sultan Ageng Tirtayasa University (Untirta) as one of the State Universities in Banten to social economy impact which is proxied by human development index and economy growth in Serang City. Generally, there are two subtansial problems. First, the impact of the existence of the Untirta campus has not much impact to the human development index Serang City. Second, the relationship between educational sector and economic growth rate requires to further study. This research uses Ordinary Less Square regression and Input-Output Analysis. According to the results of several regression models, there are consistent influence of government investment and student graduated of Sultan Ageng Tirtayasa University which lead to an increase in human development index of Serang City. Meanwhile, according to another regression model, investment has not significant influence to local economy growth. However, the student graduated of Sultan Ageng Tirtayasa University has positive relationship and significant to influence the local economy growth. Furthermore, Input-Output Analysis is an equilibrium model, where Sultan Ageng Tirtayasa University as services provide on the education sector. Education sector has ability to increase industrial growth upstream (backward linkage) and encourage the production of other sectors that use inputs from the education service sector.